Outcomes of stable HIV-positive patients down-referred from doctor-managed ART clinics to nurse-managed primary health clinics for monitoring and treatment - Brennan, Alana (2011)
OBJECTIVE: Compare clinical, immunologic and virologic outcomes amongst stable HIV-positive patients down-referred (DR) to nurse-managed primary health care clinic (PHC) for treatment maintenance to those who remained at the doctor-managed treatment-initiation site (TI). DESIGN: We conducted a matched cohort analysis amongst stable HIV patients at the Themba Lethu Clinic, in Johannesburg, South Africa. Eligible patients met the criteria for down-referral (undetectable viral load <10-months, ART >11-months, CD4 ≥200cells/mm(3), stable weight and no opportunistic infections) regardless of whether they were down-referred to a PHC for treatment maintenance between February 2008-January 2009. Patients were matched 1:3 (DR:TI) using propensity scores. METHODS: We calculated rates and hazard ratios for the effect of down-referral on loss to follow-up (LTFU) and mortality and the relative risk of down-referral on viral rebound by 12-months of follow-up. RESULTS: 693 DR patients were matched to 2079 TI patients. Two (0.3%) DR and 32 (1.5%) TI patients died, 10 (1.4%) DR and 87 (4.2%) TI were lost, while 22 (3.3%) DR and 100 (5.6%) TI experience viral rebound by 12-months of follow-up. After adjustment, patients down-referred were less likely to die (HR 0.2; 95%CI: 0.04-0.8), become LTFU (HR 0.3; 95%CI: 0.2-0.6) or experience viral rebound (RR 0.6; 95%CI 0.4-0.9) than TI patients during follow-up. CONCLUSIONS: The utilization of nurse-managed PHCs for treatment maintenance of stable patients could decrease the burden on specialized doctor-managed ART clinics. Patient outcomes for DR patients at PHCs appear equal, if not better, than those achieved at ART clinics amongst stable patients.